Performing Effective Research Using ChatGPT - Pal, Subhabaha (Indian Journal of Computer Science, 2022)
OpenAI created ChatGPT, an Artificial Intelligence based Chatbot that responds conversationally to lengthy, complicated enquiries. The present paper is a guide to how the potential of ChatGPT can be used fully to perform effective research studies in the shortest possible time.